Relatório de Estágio Profissional "O trajeto numa "Montanha Russa" de um Profissional de Educação Física" - Paulo Jorge Ribeiro de Sousa (2017)
This document aims at a critical and reasoned reflection on an experience of the Practicum (Student Teaching), in the scope of the 2nd Cycle in Physical Education Teaching in Basic and Secondary Education, at the Faculty of Sport of the University of Oporto . The Practicum (Student Teaching) is a process of singular and personal character, being a particular moment to summon all the knowledge acquired during the initial formation and to put them into practice in the real context of teaching. This Internship Report reflects the trajectory of a trainee student in a new environment, Escola Básica e Secundária D. Dinis. It is organized into seven chapters: (1) Introduction, where the purpose of this document is revealed; (2) The Personal Framework, which describes all the reasons of the student trainee that led to the choice of this training course, as well as the whole course of the course; (3) the Professional Practice Framework, where the context of the internship is explained; (4) Organization and Management of the Teaching-Learning Process, which is divided into three areas: Conception, Planning and Realization, Participation in School and Relationship with Community and Professional Development; In the latter is inserted the research study, with the theme "The Perceived Relationships of a Group through the Application of a Sociometric Test"; (5) Conclusions and Future Perspectives, which presents the final balance of the Professional Internship as well as the future aspirations of the Trainee Student (6) and (7) Bibliographical References and Annexes, respectively.